Supervisory Approaches in the Implementation of Game-Based Strategies for Numeracy Improvement - Frichelle S. Macahito; Mark Joseph Q. Espia (Journal of Innovation in Education and Social Research, 2026)
This research investigated how school leaders and master teachers in the District of Calatrava I supervise and the effectiveness of these approaches in promoting the adoption of game-based strategies aimed at enhancing numeracy in public elementary schools. The study examined demographic characteristics, supervisory practices, and the relationship between supervision and instructional outcomes. The findings indicated that most of the school heads and master teachers were academically qualified, with many having pursued advanced degrees, and professionally seasoned, possessing extensive teaching experience. Consistent application of supervisory approaches across all areas, demonstrating strong instructional leadership and dedication to supporting teachers. Game-based strategies were found to be highly effective, reflecting supervisors' ability to promote innovative teaching practices. The Analysis of Variance (ANOVA) revealed no significant differences in supervisory approaches based on age, educational attainment, or length of service. This suggests that supervisory practices are uniform and stable across different demographics. Furthermore, correlation analysis demonstrated a robust positive and statistically significant association between supervisory methods and the efficacy of game-based strategies, emphasizing the crucial role of supervision in ensuring successful implementation. In light of these findings, actionable recommendations were developed for school leaders, master teachers, educators, curriculum developers, the Department of Education, and future researchers to enhance supervisory practices and maintain innovation in numeracy instruction. The study underscored the importance of effective supervision, grounded in experience and academic training, for improving learner outcomes through game-based strategies, particularly in rural and upland settings.